Internationalisation of cluster organisations : strategy, policy and competitiveness /: strategy, policy and competitiveness. (2016) - Pavelková, Drahomíra; Bednář, Pavel; Bialic-Davendra, Magdalena; Břusková, Pavla; Knápková, Adriana; Zahradník, Petr, 1965-
No abstract available